2016
DOI: 10.1016/j.jmb.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Chemoreceptor Dynamics: Helical Stability in the Cytoplasmic Domain Varies with Functional Segment and Adaptational Modification

Abstract: Dynamics are thought to be important features of structure and signaling in the cytoplasmic domain of bacterial chemoreceptors. However, little is known about which structural features are dynamic. For this largely helical domain, comprising a four-helix bundle and an extended four-helix coiled coil, functionally important structural dynamics likely involves helical mobility and stability. To investigate, we used continuous wave EPR spectroscopy and site-specific spin labels that directly probed, in essentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 58 publications
9
40
0
Order By: Relevance
“…This agrees with our previous HDX and NMR studies on similar samples, which found MH1 dynamics in both CF4E and CF4Q to be comparable to the C terminal tail dynamics (11,14). EPR studies of site-specific spin labels measured the mobility of helices of the cytoplasmic domain of intact Asp receptor inserted into nanodiscs, but lacking CheA and CheW (16). Consistent with our results, Bartelli and Hazelbauer observed that MH1 is more dynamic than MH2.…”
Section: Diverse Dynamic Properties Of Cf In Functional Signaling Comsupporting
confidence: 92%
See 3 more Smart Citations
“…This agrees with our previous HDX and NMR studies on similar samples, which found MH1 dynamics in both CF4E and CF4Q to be comparable to the C terminal tail dynamics (11,14). EPR studies of site-specific spin labels measured the mobility of helices of the cytoplasmic domain of intact Asp receptor inserted into nanodiscs, but lacking CheA and CheW (16). Consistent with our results, Bartelli and Hazelbauer observed that MH1 is more dynamic than MH2.…”
Section: Diverse Dynamic Properties Of Cf In Functional Signaling Comsupporting
confidence: 92%
“…Peptides near the N and C termini exhibit very fast exchange, with 90-100% deuterium uptake in the first 3 minutes, suggesting these regions are highly flexible and solvent exposed. These findings are consistent with previous hydrogen exchange mass spectrometry (11) and NMR studies (14) on similar samples of functional complexes, and with electron paramagnetic resonance (EPR) on spin-labelled intact receptors in nanodiscs (16). The C-terminal tail is thought to be an unstructured, flexible tether for binding the methylation and demethylation enzymes (17).…”
Section: Figuresupporting
confidence: 90%
See 2 more Smart Citations
“…Several in vitro studies, including hydrogen-exchange MS (57), NMR dynamics approaches (58), and electron paramagnetic resonance (59)(60)(61), have demonstrated differential dynamic properties of the MH1 and MH2 helices that are consistent with the zipped-cap model. The in vivo signaling properties of truncated Tar receptors are also consistent with the zipped-cap model (62).…”
Section: Discussionmentioning
confidence: 92%